Food, culture, and identity in multicultural societies: Insights from Singapore. (1st June 2020) - Reddy, Geetha; van Dam, Rob M.
Abstract: The choice of food practices can be influenced by one's identity in many societies, but has mostly been evaluated in light of the maintenance of cultural identity in migrant populations. This study focused on understanding the influence of identity on food practices among individuals in multicultural societies. We conducted 18 focus group discussions (n = 130) among Indian, Chinese and Malay women in Singapore. Focus group transcripts were analysed using Thematic Analysis both inductively and deductively. Deductive analysis was framed within a Social Representations Approach, a social psychological theory that allows a deeper understanding of the contextual aspects of identity. Participants highlighted the central position of food in social events, cultural celebrations, and persistent traditional beliefs about health (such as 'hot-cold balance'). These beliefs extended to the perception of certain traditional foods possessing medicinal properties. Importantly, the consumption of these traditional foods was accepted as necessary for the maintenance of health by the women. We propose that while cultural food practices are integral to identity preservation and identity continuity for Singaporean women from all three racial groups, this is different to other multicultural societies such as Canada where communities preserve their cultural food practices, in part, due to fear of cultural identity loss. In addition, cross-cultural food practices are readily adopted in participants' daily lives for a number of reasons such as the promotion of health, convenience, and variety. At times, this adoption blurred boundaries between different cultural cuisines. Food practices in multicultural societies like Singapore are thus a reflection of everyday multiculturalism, multicultural social policies, and attitudes towards traditional healthful food practices, and these aspects need to be considered in the development of public health policies and interventions. Highlights: Food practices enable construction and maintenance of cultural, racial, and ethnic identities. Some traditional foods are perceived to have medicinal qualities and are consumed regularly. Traditional beliefs about the importance of foods for hot-cold balance and health affect daily food practices. Cross-cultural food practices (both cross-Asian cuisines and Western) are common and adopted for a variety of reasons. Everyday multiculturalism, and multicultural social policies influence food practices in Singapore.